Implementasi Algoritma A Star Untuk Pemetaan Fasilitas Umum Berbasis Mobile GIS Pada Kabupaten Serdang Bedagai - Fani Panca Sari; Ali Ikhwan; Suendri Suendri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid advancement of technology has significantly simplified the process of accessing essential information. Alongside the increasing population in Serdang Bedagai Regency, there has been a consistent expansion in the construction of public facilities. However, the extensive geographical area of this region poses challenges in providing accessible routes to these facilities. This study aims to implement the A* (A-Star) algorithm within a mobile-based Geographic Information System (GIS) to optimize the mapping and routing of public facilities in Serdang Bedagai Regency. By leveraging the A* algorithm, the application provides users with the most efficient and shortest routes to their desired destinations. This application is designed for easy integration with commonly used smartphones, allowing residents and tourists to navigate public facilities with greater convenience. The GIS-based platform also serves as a valuable tool for local governments to manage and analyze the distribution and accessibility of public infrastructure. The results demonstrate that the implementation of the A* algorithm effectively enhances route optimization by considering both distance and heuristic evaluations. This research contributes to improving public access to essential facilities while addressing geographic challenges within the regency.